Prevalence and Characteristics of Articular Eminence Pneumatization: A Cone-Beam Computed Tomographic Study - Khojastepour, Leila (J Maxillofac Oral Surg, 2017)
PURPOSE: The temporal bone represents a variety of pneumatization patterns with clinical significance for planning surgical procedures in this area. The purpose of the present study was to assess the prevalence and characteristics of the glenoid fossa and articular eminence pneumatization and to classify the pattern of pneumatization using CBCT images. METHODS: CBCT images of 327 patients (654 temporal bones) were evaluated to determine pneumatized articular eminence prevalence and characteristics. Gender, age, laterality, type and grade of pneumatization were recorded for the left and right sides. Chi-square test was used to evaluate the relationship between pneumatized articular tubercle and gender, grade and type. RESULTS: PAT was identified in 251 (76.7%) patients of whom 139 (55.4%) were male and 112 (44.6%) were female with a mean age of 30.31 ± 10.32 years. Bilateral PAT occurred in 175 (69.7%) patients. Three hundred and ninety-six (93%) of areas were multilacunar, and 30 (7%) were unilacunar. Of 654 areas, 228 (34.8%) had grade 0, 299 (45.7%), grade 1, 92 (14.1%), grade 2 and 35 (5.4%), grade 3. No statistically significant correlation was found between prevalence of pneumatization, gender, type and grade. CONCLUSION: The present study emphasized the need to assess PAT before surgical intervention of TMJ. CBCT provides reliable and accurate information to determine the characteristics, the exact extension of pneumatization and its relationship to the adjacent structures. The preoperative temporal bone CBCT is a crucial component of the evaluation of PAT in patients candidate for surgical intervention of TMJ.